Assessing and communicating heterogeneity of treatment effects for patient subpopulations: Keynote and panel discussion on communicating heterogeneous treatment effects across populations. (4th May 2021) - Heyward, James; Lolic, Milena; Spong, Catherine; Atkins, David; Pennello, Gene; Varadhan, Ravi
Abstract: How do we communicate nuanced regulatory information to different audiences, recognizing that the consumer audience is very different from the physician audience? In particular, how do we communicate the heterogeneity of treatment effects ‐ the potential differences in treatment effects based on sex, race, and age? That is a fundamental question at the heart of this panel discussion. Each panelist addressed a specific "challenge question" during their 5‐minute presentation, and the list of questions is provided. The presentations were followed by a question and answer session with members of the audience and the panelists.